DEVELOPMENT OF FIQH LEARNING MEDIA BASED ON LITERACY SKILLS USING A MAGAZINE MODEL TO IMPROVE THE LEARNING OUTCOMES OF STUDENTS AT MADRASAH IBTIDAIYAH IN THE SOUTHERN PADANGSIDIMPUAN DISTRICT - Nurhidayani Siregar; Muhammad Darwis Dasopang; Fauziah Nasution (Universitas Islam Negeri Sumatera Utara, 2025)
The purpose of this study is to develop a Fiqih learning medium in the form of a magazine to improve student learning outcomes at Madrasah Ibtidaiyah in Padangsidimpuan District. This study uses a research and development method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The development process includes needs analysis, material design, media development, learning implementation, and evaluation of results. The study was conducted at the Madrasah Ibtidaiyah in Padangsidimpuan Selatan District, with 25 fifth-grade students as the test subjects. The data collection instruments used were observation, interviews, tests, questionnaires, and documentation, along with techniques for analyzing validity, effectiveness, and practicality. The research results indicate that the developed media are deemed suitable based on validation by subject matter experts, media experts, and language experts as follows: (1) the quality of the developed media was rated 93.6% by subject matter experts, 89.5% by media experts, and 87.5% by language experts. (2) The results of student responses through pre-test and post-test questions yielded a percentage of 86.2%. In this regard, it was deemed suitable and effective for use in Fiqh education. (3) It can be concluded that the Fiqh educational media in the magazine model is beneficial for students and suitable for use as educational media for Fiqh